Marginality and social Integration in Uruguay - Fuben Kaztman (CEPAL Review, 1997)
Within Latin America, Uruguay stands out by its equalitarian income distribution, the solidity of its democratic institutions, and its level of social integration. Over the last decade, however, there have been signs of cracks in this desirable image which adversely affect the harmony of social relations. These cracks take the form of marginal behaviour: i.e., types of behaviour which are not governed by socially accepted patterns. In this study, the explanation for these types of behaviour has been sought in the divergences between cultural goals, the structures of opportunities for attaining those goals, and the shaping of individual capacities for taking advantage of them. A central premise of the approach adopted is that the factors determining marginal forms of behaviour build up their effects in a cyclical manner throughout the different stages of individual lives and from generation to generation.